The meaning of life - Eagleton, Terry, 1943- (New York : Oxford University Press, 2007)
Explores how thinkers throughout history have tried to answer questions about the true meaning of life, and explains why the question has become particularly difficult in modern times.
Includes bibliographical references (p. [176]-181) and index.
Library Journal.
Adult
Keywords: Life; Meaning (Philosophy); Life; Philosophy